An African city and the modern plague: transformations in governance at the moment of Mbabane's HIV & AIDS crisis - Marrengane, C. Ntombini (Unknown, 2025)
This study examines the governance of Mbabane, Eswatini, a Southern African city, at the height of the global HIV epidemic (1995–2005), which cut through the continent like an unstoppable plague. Located at the epidemic's epicentre, the Kingdom of Eswatini held the unfortunate distinction of having the highest infection rate in the world, with one in every three adults testing positive at the end of the 20th century. Such devastating numbers required a response at every level of government. This study looks at the intersection between governance and the crises unleashed by a modern plague at an urban scale. In response to the devastating effects of the epidemic on city residents, Municipal Council of Mbabane (MCM) officials adopted innovative strategies to mitigate the epidemic's impact, extending beyond the city's legal mandate. Through a deliberate process, the council reoriented its focus away from its core mandate of command and control of urban space to engaging and experimenting with city residents, civil society organisations and, most importantly, traditional authorities who directly influenced the expansion of the city and yet remain excluded in meaningful ways from urban management. By adopting this novel approach, the MCM found ways to align its service delivery mandate with the unprecedented needs emerging at the household level because of the unfolding HIV epidemic. This study uses qualitative methods, to explore the extraordinary efforts of city officials to govern the city during crisis through ‘incremental bricolage' – a term used to define the governance processes that emerged in a complex urban setting amid a crisis. This term describes the provisional, collaborative, and collective decision-making across institutional structures in an environment of bifurcated governance. Incremental bricolage provided a pathway for the council's engagement with traditional authorities, an influential but long ignored urban stakeholder. Incremental bricolage also offered new opportunities for the council to develop partnerships to meet the changing needs of urban residents because of the deadly plague. By repurposing relationships and capacities within the council and across organisations outside the municipality, the governing body led a process of rationalising and equitability extending the reach of HIV support and care services across the city. Disrupting the notion of dysfunctional governance systems in African cities, this case draws attention to the conditions under which urban local authorities operate. This case also highlights the flexibility and innovation demonstrated by MCM officials and other key governance stakeholders to meet the iv needs of city residents in a bifurcated urban context at a moment of crisis triggered by a global epidemic.